Impact on Ant Communities by Chemical Pesticides Applied in Controlling the Red Imported Fire Ant (Solenopsis invicta Buren) in the Field - Yunbo Song; Meng Chen; Jiarui Wu; Jingxin Hong; Ting Ouyang; Yuling Liang; Mingrong Liang; Yongyue Lu (Insects)
The red imported fire ant (RIFA, Solenopsis invicta Buren) represents a significant invasive pest in China, exerting extensive negative impacts on ecosystems. The invasion of RIFA not only poses a severe threat to biodiversity within the environment; inappropriate controlling measures can also adversely affect community dynamics. Therefore, while implementing effective management strategies to control the proliferation of RIFA populations, it is imperative to evaluate the potential effects of these measures on the structure of local biological communities to safeguard native biodiversity. This study employs a “two-step method” using dust and bait formulations, respectively, to control RIFA while conducting ecological monitoring to further assess the impact of RIFA population decline on ant communities. The results of RIFA management showed that after post-treatment periods of 28 days, 35 days, and 60 days, the worker ant reduction rates for the three insecticides—0.5% beta-cypermethrin dust, 1.0% hydramethylnon bait, and 0.1% indoxacarb bait—reached approximately 72%, with their efficacy ranked as follows: 1.0% hydramethylnon bait > 0.1% indoxacarb bait > 0.5% beta-cypermethrin dust. By the 60th day of the experiment, the ant nest reduction rates reached their highest values—66.84% for 0.5% beta-cypermethrin dust, 77.89% for 1.0% hydramethylnon bait, and 87.52% for 0.1% indoxacarb bait—with the latter performing the best. Meanwhile, the occurrence level of RIFAs in all three pesticide treatment areas decreased from level III to level I 60 days post-treatment. Following the application of these three insecticides, the RIFA population significantly decreased, leading to an increase in species richness within the ant community. The reduction in RIFA numbers had a positive impact on the restoration of ant community diversity, as evidenced by significant improvements in both diversity and evenness indices. Notably, 0.1% indoxacarb bait was particularly effective in enhancing the ant community diversity and species richness, while 1.0% hydramethylnon bait was more effective in improving community evenness. These findings indicate that the controlling strategy used in this study not only effectively manages RIFA populations but also promotes recovery and contributes to the ecological balance of local ant communities, providing an important reference for future biodiversity conservation efforts.